Lower Devonian Amphipora of the Muruntau Mountains (Central Kyzilkum) - Karimova Firdaus Sabirovna (Genius Journals, 2023)
The results of the study and a monographic description of the amphiporides of the Tamdytaumountains are presented. The sections are characterized by carbonate deposits, in which amphipores characteristic of the Lower Devonian of a subcylindrical form are observed. Amphipores are not only rock-forming, but also a good benchmark for identifying Lower Devonian deposits.
Keywords: amphipores; Lower Devonian; Muruntau; Dzhengeldinskaya Formation